The construction sector in the Ecuadorian economy, importance and perspectives - Díaz-Kovalenko, Igor Ernesto (2022)
The research reflects the relevance of the construction sector within the Ecuadorian economy, especially its strong influence on the country's current economic situation. Being a fundamental sector of the economy, it can be considered as an indicator of the country's situation. For this work, different national official sources are used with the objective of analyzing the contribution and relevance of the economic activity of construction and its effect on several national macroeconomic indicators. The construction sector is highly sensitive to the economy, as it is labor intensive and attracts foreign direct investment. In addition, it is important to highlight the high linkage effect it has with the input supply sectors, as well as with financial institutions. It is concluded that in Ecuador this sector is a dynamic activity of the country's productive apparatus and therefore: 1) it is important to have sufficient stability, generated through public policies; 2) solve the pent-up demand for housing; 3) generate confidence in the financial system; and 4) establish preferences for real estate investments to encourage the reactivation of this sector, as well as the economy as a whole.